Analisis Status Mutu Air Sungai Solomeronda Sebagai Sumber Air Baku Perusahaan Daerah Air Minum (PDAM) Kabupaten Konawe Provinsi Sulawesi Tenggara - Rafidah Imran; Hasim Danuri; Mohammad Yanuar Jarwadi Purwanto (President University, 2022)
Abstract. The Solomeronda River is a water source that currently supplies the clean water needs of the residents of Konawe Regency, with a very useful function for the community, namely for bathing, cooking and as a source of raw water for Regional Drinking Water Companies (PDAM). However, the Solomeronda River is still affected by several community activities that can reduce the quality of river water, such as felling trees and disposing of organic and inorganic waste into river bodies. These community activities will certainly affect the water quality of the Solomeronda River. Purpose: To analyze the status of river water quality through water sampling. Methods and results: Analysis of water quality status was carried out by taking water samples at three stations, namely station I (upstream), station II (middle), station III (downstream) and analyzed in the laboratory with water quality parameters analyzed including physical parameters, chemical parameters and microbiological parameters. The results of water quality measurements were then analyzed using the pollution index method. The results showed that the pollution index of the Solomeronda River at station I was 0.87 (meets quality standards), station II was 0.91 (meets quality standards) and station III was 1.1 (lightly polluted). Conclusion: Overall the pollution index value of the three stations on the Solomeronda River after being averaged has a value of 0.96, it is concluded that the status of the water quality of the Solomeronda River is included in the classification of meeting quality standards (good condition).